FORMATION OF KNOWLEDGE AND SKILLS ABOUT COUNTRY STUDY IN TRANSLATION (TAMADDUN NURI JURNALI, 2024)
This article analyzes the relationship between regional studies and translation. Firstly, an attempt is made to refer to the terms of regional studies; Since there are many definitions, only a few of them will be discussed in this article.